2018
DOI: 10.1038/s41598-018-24536-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights into aluminum-tolerance pathways in Stylosanthes as revealed by RNA-Seq analysis

Abstract: Stylo has a great potential for Al3+ resistance in acidic soils through secretion of citrate from the roots. To get insight into the molecular mechanisms responsible, transcriptomic changes were investigated in the roots after treatment with T01 (−Al3+, pH6.0), T02 (−Al3+, pH4.3) and T03 (50 µM AlCl3, pH4.3). In total, 83,197 unigenes generated from 130,933 contigs were obtained. Of them, 282, 148 and 816 differentially expressed unigenes (DEGs) were revealed in T01_vs_T02, T02_vs_T03 and T01_vs_T03 comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…DAG, Ca 2+ and protein kinases [9]. Proteins associated with the G-protein-mediated signaling pathway, DGAT and kinase cascades (CPK1 and CKI) were detected in the present study (S1, S2 and S8 Tables).…”
Section: Plos Onesupporting
confidence: 57%
See 1 more Smart Citation
“…DAG, Ca 2+ and protein kinases [9]. Proteins associated with the G-protein-mediated signaling pathway, DGAT and kinase cascades (CPK1 and CKI) were detected in the present study (S1, S2 and S8 Tables).…”
Section: Plos Onesupporting
confidence: 57%
“…For decades, a number of proteins contributing to Al 3+ tolerance have been identified in plants, and many studies have provided direct evidence linking Al 3+ -induced OA exudation from plant roots to malate and citrate efflux transporters (ALMTs), multidrug and toxic compound extrusion proteins (MATEs) and H + -ATPase activity in the plasma membrane [ 1 , 8 ]. In Stylosanthes roots, our recent data revealed that the signaling cascades of Al 3+ -induced citrate exudation comprise heterotrimeric G-proteins, phosphoinositide phospholipase C (PLC), inositol triphosphate (IP 3 ), diacylglycerol (DAG), Ca 2+ and protein kinases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transcriptome and proteome profiles have been used to analyze the responses of stylo to Al and Mn toxicity [47][48][49]. However, metabolic alterations of stylo roots in response to P deficiency have yet to be reported.…”
mentioning
confidence: 99%
“…and Mn toxicity [47][48][49]. However, metabolic alterations of stylo roots in response to P deficiency have yet to be reported.…”
Section: Recently Transcriptome and Proteome Profiles Have Been Usedmentioning
confidence: 99%